Contos de fadas tradicionais e renovados : uma perspectiva analítica - Alberti, Patrícia Bastian (My University, 2015)
This investigation proposes a comparative analysis of the books Cinderella, by Charles Perrault, Cinderella by Jacob and Wilhelm Grimm and Cinderella: the authorized biography, by Paula Mastroberti, aiming to verify the transformations each version has suffered due to the influences from the regional culture, the space and the historical context that they represent. Considering that these books are ch ildren's interest, the essential aspects of this genre will be reviewed. The task is divided in four parts: the first one discusses the basic questions that involve the genre tale and its conceptual approximations; the second approaches basic concepts about children's literature and chi ldhood; the third presents the problematic of the regionality, associating it with the Brazilian and South Brazilian chi ldren's literature; and the fourth analyses the texts that compose the corpus of this research. The conclusion aims to point out, through the analyzed books, the relations between traditional and renovated children 's literature and also between children 's literature and regionality.
Esta investigação propõe uma análise comparativa das obras Cinderela ou Sapatinho de Cristal, de Charles Perrault; Cinderela, de Jacob e Wilhelm Grimm e Cinderela: uma biografia autorizada, de Paula Mastroberti, com a finalidade de constatar as transformações que ocorreram em cada versão devido à influência da cultura regional, do espaço e do contexto histórico que representam. Tratando-se de obras de interesse infantil, são revisados aspectos fundamentais dessa modalidade de literatura. O trabalho está dividido em quatro partes: a primeira discute as questões básicas que envolvem o gênero conto e suas aproximações conceituais; a segunda aborda conceitos básicos sobre literatura infantil e infância; a terceira apresenta a problemática da regionalidade, associando-a com literatura infantil brasileira e riograndense; e a quarta, analisa os textos que compõem o corpus desta pesquisa. A conclusão procura, por meio das obras analisadas, assinalar as relações entre literatura infantil tradicional e renovada e entre literatura infantil e regional idade.
Keywords: Contos de fadas; Literatura infantil - Crítica; Paródia; Fairy tales; Children's literature - Criticism and interpretation; Parody